Development of Water Transplant Based Single Core Osmotic Pump for Fluvoxamine Maleate Employing Quality by Design Principles (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The present study draw a bead on preparing single core osmotic pump with improved water transplant by employing Quality by Design (QbD) principles to achieve zero order drug release for prolonged period of time. QbD principles were employed in preparing single core osmotic pump by deriving quality target product profile (QTPP), critical quality attributes (CQA) followed by risk assessment using ishikawa diagram and risk estimation matrix. Box-Behnken Design was employed to study the effect of various independent parameters like concentration of Natrosol 250 HX (X1) and concentration of Xylitab (X2) no. of orifice (X3), on various dependent parameters like lag time (Y1) and time required for release 25%, 50%, 75% and 100% drug (Y2, Y3, Y4 and Y5). A controlled space was designed where each criteria or CQA was satisfied. Optimized formulation was further characterized for its efficiency. The results of design suggest the suitability of design for optimization of single core osmotic pump. In the initial period, drug release was driven by no. of orifice which on later stage depends on concentration of swellable polymer and concentration of osmogen. Optimized design was validated by preparing check point batch having less than 5% predicted error. Model fitting with drug release kinetics showed that optimized single core osmotic pump released drug in zero order. Stability data suggested that prepared formulation was stable for 3 month period without significant changes in the CQA. Single core osmotic pump using water transplant was successfully developed for a poorly soluble drug using QbD principles.